The World’s Evangelical Alliance and the Spanish Civil War - Hale, F (Acta Theologica, 2000)
British Christians reacted variously to the Spanish Civil War (1936-1939) and crossed verbal swords in the campaign for the hearts and minds of the public over this heated issue at a time when many people believed that Western civilisation and the future of Christianity in Europe were hanging in the balance. Generally speaking, Roman Catholics in the United Kingdom, alarmed at the violence which anticlerical mobs inflicted on religious personnel in parts of Spain and concerned about their denomination’s loss of its privileged status, supported the insurgency of General Francisco Franco, leader of the ultimately victorious Nationalist forces. In the Church of England opinion was divided. In various Nonconformist circles, there was considerable support for Republican Spain. The interdominational Evangelical Alliance, founded in England in 1846 inter alia to promote Protestant interests internationally at a time when the Roman Catholic Church was perceived as a threat to religious freedom in Europe and elsewhere, lent its voice to the Republican cause. This was by no means a matter of ideological sympathy for the socialism of the Madrid regime, but reflected the Evangelical Alliance’s traditional support of the Protestant churches in Spain, whose hard-won freedom, it was believed, would be threatened by a Nationalist victory and the restoration of Roman Catholicism as the official religion of the realm.